Mifepristone and misoprostol in pregnancy termination in hyperthyroid patients - Sud, Shyam Sunder; Bhatnagar, Mini; Sud, Nishi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Incidence of clinical hyperthyroidism in pregnant patients has been reported as 0.25-2.8%. They may be anxious and may not opt for surgical methods of medical termination. Medical termination of pregnancy by Mifepristone and Misoprostol is increasingly being used. We do not know the efficacy of this method in hyperthyroidism.